2015
DOI: 10.1557/jmr.2015.23
|View full text |Cite
|
Sign up to set email alerts
|

Ion-beam irradiation and 244Cm-doping investigations of the radiation response of actinide-bearing crystalline waste forms

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The high loading of U within this phase also suggests the potential of materials adopting the garnet-type structure to be nuclear waste forms. It is notable that garnet-type materials have been synthesized that contain a high concentration of U (∼30 wt % U). ,, A considerable amount of work has been completed to study the stability of actinides in garnet against radiation damage and corrosion resistance. , However, factors that affect the oxidation states in garnet-type oxides have not been addressed. The incorporation of radioactive actinides with varying oxidation states into nuclear wasteforms is also of importance. ,, The substitution of U or Pu into garnet is complex because of the variable oxidation states of these elements, which can be studied by investigating Ce-containing garnet-type materials because Ce behaves in a manner similar to that of some actinide elements (e.g., Pu). , …”
Section: Introductionmentioning
confidence: 99%
“…The high loading of U within this phase also suggests the potential of materials adopting the garnet-type structure to be nuclear waste forms. It is notable that garnet-type materials have been synthesized that contain a high concentration of U (∼30 wt % U). ,, A considerable amount of work has been completed to study the stability of actinides in garnet against radiation damage and corrosion resistance. , However, factors that affect the oxidation states in garnet-type oxides have not been addressed. The incorporation of radioactive actinides with varying oxidation states into nuclear wasteforms is also of importance. ,, The substitution of U or Pu into garnet is complex because of the variable oxidation states of these elements, which can be studied by investigating Ce-containing garnet-type materials because Ce behaves in a manner similar to that of some actinide elements (e.g., Pu). , …”
Section: Introductionmentioning
confidence: 99%
“…The limitations faced by internal irradiation can be overcome using an external irradiation method in which the radiation events are simulated under laboratory conditions via high energy ion implantation. , In this method, the radiation conditions representing different time periods of HLW storage are attained in a very short time by irradiating a thin region of the monolithic wasteform (e.g., pellet) with high-energy ion beams (e.g., He 2+ , Ne + , Kr + , Au – ) of varying ion doses (i.e., number of ions/cm 2 ). , The externally irradiated solids are also nonradioactive, which therefore allows the use of different experimental techniques to characterize the ion-implanted solids . Since α-decay is the major decay pathway for actinides present in HLW, the wasteforms are irradiated with high-energy light (e.g., He 2+ ) and/or heavy (e.g., Pb + , Au – ) ions to simulate radiation effects due to α-particles and/or α-recoil atoms (i.e., daughter products), respectively …”
Section: Radiation Effects In Nuclear Wasteformsmentioning
confidence: 99%
“…8 As a result, several studies have focused on investigating the radiation damage in solid wasteforms due to α-recoil atoms. 11 The extent of structural damage due to α-decay events varies depending on the dose (i.e., number of α-decay events per gram of actinide) and type of nuclear wasteform that is being studied. 7 Structurally, glass-based host matrices in which atoms are arranged in a random fashion are less affected by the atomic rearrangements that occur as a result of α-decay of actinides.…”
Section: Radiation Effects In Nuclear Wasteformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Garnet ceramics also have excellent corrosion resistance. 12,19,28 In terms of radiation resistance, Livshits et al 29,30 found the garnet structure's radiation response is structurally constrained, which means that different compositions of garnet waste have similar radiation tolerance. Hence, garnet-based ceramics could be considered as a potential matrix for immobilizing HLW.…”
Section: Highlightsmentioning
confidence: 99%